2001
DOI: 10.1183/09031936.01.00252501
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of asthma today: Table 1

Abstract: The current concept of asthma therapy is based on a stepwise approach, depending on disease severity, and the aim is to reduce the symptoms that result from airway obstruction and inflammation, to prevent exacerbations and to maintain normal lung function.b 2 -Adrenoceptor agonists and glucocorticoids are at present the most effective drugs for the treatment of airway obstruction and inflammation, with theophylline, leukotriene receptor antagonists and anticholinergics as second-or third-line therapy. There ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…They found that the H1-receptor antagonist triprolidine was ineffective, and CysLT-or TP-receptor blockade was effective only in some cases. These findings are in line with no proven and documented benefit of antihistamines in asthma [48], and with the clinical observations of CysLT1-and TP-receptor antagonists being effective only in subsets of patients [46][47][48][49][50][51]. Notably, however, simultaneous blockade of CysLT-and TPreceptors provided nearly complete protection from antigeninduced airway contraction in PCLS from all individuals.…”
Section: Mediators Of the Early Allergic Responsesupporting
confidence: 65%
“…They found that the H1-receptor antagonist triprolidine was ineffective, and CysLT-or TP-receptor blockade was effective only in some cases. These findings are in line with no proven and documented benefit of antihistamines in asthma [48], and with the clinical observations of CysLT1-and TP-receptor antagonists being effective only in subsets of patients [46][47][48][49][50][51]. Notably, however, simultaneous blockade of CysLT-and TPreceptors provided nearly complete protection from antigeninduced airway contraction in PCLS from all individuals.…”
Section: Mediators Of the Early Allergic Responsesupporting
confidence: 65%
“…The relative contributions of the individual mediators may well differ along the airway tree and be related to differences in amounts of released mediators, airway geometry and expression of receptors. Again, when all three classes are blocked, there is complete protection [7,9,30,32,35].…”
Section: Guinea Pig Precision-cut Lung Slicesmentioning
confidence: 99%
“…Therefore, higenamine was markedly effective in reducing the severity of bronchoconstriction following the exposure of guinea pigs to atomized histamine solutions. β 2 -AR agonists, as bronchodilators, have been used for the relief and prophylaxis of asthma for more than 30 years [1] . On the other hand, there are hundreds of different kinds of herbs used for the treatment of asthma in TCM.…”
Section: Properties Of the Choβ 2 -Ar-cre-egfp Cells Assay System β 2mentioning
confidence: 99%
“…Beta2-adrenergic receptor (β 2 -AR) agonists have been used for the relief and prophylaxis of asthma symptoms for many years [1] . The β 2 -ARs are mainly located in the alveolar walls [2] and mediate the relaxation of human airway smooth muscle in vivo and in vitro [3] .…”
Section: Introductionmentioning
confidence: 99%